Model Dialog dalam Syair Asta’an di Desa Alassumur Kulon, Kraksaan: Kajian Ekolinguistik - Hamdiah, Magfirotul; Harja Susetya, Hemas Haryas; Aisyah, Siti (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
Abstract The dialogue model is often used in everyday life. The dialogue model is always related to the surrounding environment. One type of dialogue that is often heard is in the poetry of Astaan. Astaan poetry is a poem or song that has the meaning of praising the creator of the universe and contains a motivational sentence. The aim of this research is to find out the meaning of poetry that is often used by the people of Alassumur and its relationship to the social environment. The research method used is descriptive qualitative. The data collection technique is by taking notes and analyzing it using the theory of the social environmental dialogue model. The results of the research found the meaning of praising the creator of the universe and contained a motivational sentence. Examples of data contained in Astaan poetry are jhue agi jealousy, atenah dirty foreigner, iman lontor, immoral kaberek katemor, prostrate ethinah, nabeng dhuntak busy bhen areh, nyare esesah tabuk, moah colmot tak awuduk, penyaket ateh, nyaleh tetanggeh, moso Bik Tretan, Reng Tau Erosoro, Disobedient Dek Reng Tuah, Atobet Ma Bhekus Kalakuan. Therefore, this Astaan poem can be used as an object for ecolinguistic study.  Keywords: praise; dialogue model; poetry